2D and 3D analyses of an embankment on clay improved by soil–cement columns. (July 2015) - Chai, Jin-Chun; Shrestha, Sailesh; Hino, Takenori; Ding, Wen-Qi; Kamo, Yukihiko; Carter, John
Abstract: The behaviour of a test embankment constructed on a soft clayey deposit in Saga, Japan, was simulated by both three-dimensional (3D) and two-dimensional (2D) finite element analyses (FEA). Floating soil–cement columns had been installed in the clay prior to construction of the embankment. Comparing the results of 3D and 2D FEA indicates that 2D analysis predicts incorrect results in terms of the lateral displacement and bending moment in the columns under the toe of the embankment. In the 2D analysis, the rows of columns were modelled by continuous walls, which partially block the interaction between the soil layers and the columns and influence the simulated lateral displacement and bending moment in the column. It has been postulated that compaction of fill material during the construction process has a significant influence on both the magnitude and pattern of the lateral displacement of the column under the toe of the embankment. Pragmatically, this influence can be indirectly simulated by reducing the stiffness and increasing Poisson's ratio of the embankment fill material. Finally, both the measured and FEA results indicate that the columns not only reduced the total settlement but also accelerated the settlement rate of the deposit under the embankment loading, due to the much higher stiffness of the column material.